CONSTRUCTING TESTS FOR SHOOTING AND PASSING SKILLS IN AMPUTEE FOOTBALL PLAYERS - Imad Abd Hussein; Prof. Dr. Muthanna Ahmed Khalaf (Proximus Journal Publishing, 2025)
This study is aimed at: 1. Construct tests for shooting and passing skills in amputee football players. 2. Develop standardized tables and normative levels for these skills in amputee football players. The researchers used the method of a descriptive survey. For the 2024–2025 season, 90 amputee football club players from Baghdad, Central Euphrates, Nineveh, and Basra (not including the Kurdistan Region) were included in the research population. The eleven goalkeepers were not allowed to play since their impairment (upper limb amputation) was different from that of the other field players (lower limb amputation). There were seventy players in the final sample after nine individuals were eliminated because of injuries
Keywords: Construction; Shooting; Tests; Passing